THE EFFECTIVENESS OF CORRUPTION CRIME INVESTIGATIONS IN THE SECTOR OF PROCUREMENT OF GOVERNMENT GOODS AND SERVICES (Case Study at Poso Police) - Habibi, Habibi; Rahman , Sufirman; Sahban , Sahban (IBLAM LAW REVIEW, 2023)
This study aims to: 1) find out and analyze and evaluate the effectiveness of the investigation into corruption in the field of procurement of government goods and services in the jurisdiction of the Poso Police and 2) To find out and analyze and evaluate the factors that influence the implementation of the investigation of corruption in the procurement of government goods and services in the jurisdiction of the Poso Police. This study uses a juridical-empirical type of research because the emphasis is on examining the effectiveness of investigations into criminal acts of corruption in the procurement of government goods and services in the jurisdiction of the Poso Police. So, the data needed in this study are primary and secondary. The data collection technique is by conducting interviews to obtain valid data. The results of the study show that: 1) The effectiveness of the Investigation of Corruption Crimes in the Procurement of Government Goods and Services in the jurisdiction of the Poso Police is less effective because of several obstacles such as limited investigator resources, limited laws, limited facilities and infrastructure, and limited information from the community; and 2) Factors influencing corruption law enforcement by investigators from the Poso Police Tipikor Unit in handling corruption cases, namely human resource factors and legal structures, internal and external constraints, while internal constraints are quantity, quality and facilities and infrastructure factors, while external constraints namely Intervention Factors (political) and public support or public trust is still lacking.